2020
DOI: 10.1002/ieam.4256
|View full text |Cite
|
Sign up to set email alerts
|

Methodologies and Management Framework for Restoration of Wetland Hydrologic Connectivity: A Synthesis

Abstract: Under the dual influences of high‐intensity anthropogenic activity and climate change, wetland hydrologic connectivity (HC) has decreased significantly, resulting in the severe fragmentation of wetlands, a decrease in wetland area, and a degradation of hydrological functions, resulting in a worsening disaster response to floods and droughts. Dynamic changes in wetland HC are affected by a variety of factors. Many degraded wetlands have undergone measures to restore HC. Recovery can improve the HC pattern of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 140 publications
(185 reference statements)
1
14
0
Order By: Relevance
“…Managers should also consider leaving several stands of cattail, given that certain species (e.g., Marsh Wren) benefit from the structure these patches of taller emergent vegetation provide (Kroodsma & Verner, 2020). Because our study indicated that Least Bittern, Swamp Sparrow, and Common Gallinule may be area‐sensitive, we recommend that managers seek opportunities to increase wetland connectivity and “defragment” wetlands (Meng et al, 2020). Greater connectivity may increase breeding opportunities for these species.…”
Section: Discussionmentioning
confidence: 99%
“…Managers should also consider leaving several stands of cattail, given that certain species (e.g., Marsh Wren) benefit from the structure these patches of taller emergent vegetation provide (Kroodsma & Verner, 2020). Because our study indicated that Least Bittern, Swamp Sparrow, and Common Gallinule may be area‐sensitive, we recommend that managers seek opportunities to increase wetland connectivity and “defragment” wetlands (Meng et al, 2020). Greater connectivity may increase breeding opportunities for these species.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Russell et al [11] used basin topography to forecast the potential for wetland rehabilitation in the basin of the San Luis Rey River in southern California. Meng et al [39] highlighted the optimization of hydrological communication patterns to rehabilitate the degraded wetlands. However, these studies considered the rehabilitation potential from only a single dimension, that of hydrological condition.…”
Section: Discussionmentioning
confidence: 99%
“…were found degraded in most of the selected wetlands. Hydrological strength is fundamental to an aquatic ecosystem (Meng et al, 2020;Li et al, 2021). Since the wetlands witnessed the adverse impact of hydrological transformation, often promoted some other associated causes like habitat quality change, water pollution, biodiversity loss, etc.…”
Section: Identifying Associated Modification In Some Specific Casesmentioning
confidence: 99%